Interrelation of morphometric and biochemical changes in oral mucous membrane in animals with gastroduodenitis depending on the inflammatory response - Ihor Mysula; Valentyna Bondarchuk; Gustaw Wójcik; Walery Zukow; Nataliya Sydliaruk; Yuriy Mysula; Marianna Mysula (Kazimierz Wielki University, 2019)
Introduction. There is noconsensus opinion regarding the connection of morphometric and biochemical changes in oral mucous membrane of animals with gastroduodenitis depending on the type of inflammatory response. For this reason, it remains important to study the relationship between changes in the morphometric parameters of the oral mucosa, lipid peroxidation indices and the antioxidant system under the influence of various types of inflammatory reaction in the conditions of experimental gastroduodenitis. Material and methods. Experiments were carried out on 42 white male rats weighing 180-200 g housed under normal conditions on a standard vivarium diet; acute gastroduodenitis was simulated for 7 days by inserting by the probe into the stomach 0.25 ml of 10% solution C2H5OH and after 5 minutes 0.5 ml of 1.25% solution of HCl. Three different types of inflammatory response were also modeled. Results. The most significant changes in oral mucosa on the basis of morphometric and biochemical parameters were found in animals with hyperergic type of inflammatory reaction. Rats with hypoergic type of inflammatory reaction had a lower depth of morphometric and biochemical changes. Morphometric changes were most significant on the tenth day of the experiment, regardless of the type of inflammatory reaction. Conclusions. The obtained results confirm that changes in morphometric and biochemical parameters depend on the type of inflammatory reaction.